Ultra-ortodoksi og pluralisme - Steensgaard Paludan, Peter (Nordisk judaistik/Scandinavian Jewish Studies, 2002)
One of the central characteristics of the thinking and political practice of Israeli Ultra-Orthodox or Haredim is their rejection of internal Jewish pluralism, an attitude connected to their confrontational strategy towards the cultural aspects of modernity and consequently of modern interpretations of Judaism as found in Reform and Conservative Judaism. The following article is a description and analysis of the treatment of subjects related to Reform and Conservative Judaism in the Haredi press in particular in the ‘Lithuanian’ daily newspaper Yated Neeman as well as in the publications of its founder, the late Rabbi Eliezer Menahem Shakh. The subject is often treated extensively in editorials and articles in the Haredi press, when special events in Reform or Conservative communities in or outside Israel are catching the attention of the editorial board or subjects related to these communities arrive at the political agenda of the State of Israel. Series of articles have e.g. been caused by High Court decisions ordering the authorities not to prevent Reform and Conservative representation in the local religious councils or to finance theirs institutions etc. The articles bear the imprint of a strikingly demonizing attitude towards the Non-Orthodox movements. This attitude is derived from the premodern Haredi view that the content of their belies constitutes an absolute truth which has only one legitimate interpretation and that only this particular interpretation rightfully can bear the name Judaism.